Eternity - Sode Funch, Bjarne (Psyke & Logos, 2023)
Great mountains such as Fujiyama and Kilimanjaro are recognized as being sacred places. In myths they are aften inhabited by gods, living in eternity far above the secular life of human beings. In this article the psychological background of the images of eternity is traced, defining a transcendental experience of the mountain landscape as a creative source. A phenomenological description of a personal experience of the mountain range in the Grand Teton National Park is analyzed with the background of Jour different definitions of the transcendent experience. It is put forward that visual and emotional qualities, relating specifically to the experience of mountains, are origins of the images of eternity in myths and pictures of art and these images, as well as the mountain landscape itself, provoke personal integrity within an existential theme of eternity.